REGIONAL DISPARITIES IN SELF‐REPORTED HEALTH: EVIDENCE FROM CHINESE OLDER ADULTS. (9th May 2013) - Mu, Ren
ABSTRACT Despite the subjectivity inherent in individuals' interpretation of good health, self‐reported health is widely used in health‐related studies. With data from the pilot survey of the new China Health and Retirement Longitudinal Study, this paper applies the vignette method to control for differences in individual response scales and examines regional differences in self‐reported health among the elderly in China. The results show that people in different provinces seem to use different criteria when assessing their health conditions. Regional health disparities are underestimated if differentials in response scales are not accounted for. A substantial share of the disparities cannot be explained by the observed differences in respondents' chronic health condition, demographic characteristics, and household wealth, a finding confirmed by a test based on inpatient‐care information. Copyright © 2013 John Wiley & Sons, Ltd.